Design and evaluation of cooling workwear for miners in hot underground mines using PCMs with different temperatures - Zheng, Qing; Ke, Ying; Wang, Hongfu (International journal of occupational safety and ergonomics, 2022)
Cooling workwear using phase change materials (PCMs) was designed for miners in hot underground mines. A new arrangement of PCM packs was introduced that used 15 °C PCMs as the inner layer and 23 °C PCMs as the outer layer (15&23). Its performance was investigated using thermal manikin and human subject tests by comparison with clothing without PCMs (CON), with 15 °C PCMs (15&15) and with melted PCMs (mPCM) in a climate chamber (30 °C, 80% relative humidity). The PCM cooling workwear significantly increased the manikin heat loss, attenuated the rise of skin temperatures and improved thermal sensation and comfort. The cooling duration was extended in 15&23 as compared with 15&15. The added PCMs did not affect the perceptual exertion and body mobility. In summary, cooling workwear using PCMs with different temperatures can be an effective option for miners' personal cooling in a hot and humid environment.